Is it necessary to modify science learning for autistic children? - Nugroho, Ikhlasul Ardi; Tiarani, Vinta Angela; Hastuti, Woro Sri; Supartinah, Supartinah (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
Modifying the curriculum is often necessary for autistic children to effectively engage in their learning. Interestingly, a particular learning process was discovered that proved to be effective without any need for modification - specifically, teaching science to an autistic child. This discovery calls for further investigation. This study aims to provide a comprehensive description of the unique traits exhibited by autistic children who excel in learning science without the need for any modifications. This study utilized the Spradley analysis method, which involves domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The participants in this study consisted of elementary school students in the 3rd grade who have autism. They were selected using the purposive sampling method. The data collection involved conducting interviews, examining documentation, and studying artifacts. The findings of the study indicate that children with mild autism can effectively learn science without requiring any adjustments, while still receiving necessary accommodations. Tasks can be effectively completed with the support of teachers and the assistance of paraprofessionals. Autistic children demonstrate proficiency in basic science process skills, creativity, and fine motor skills. They also exhibit a positive affect and are able to socialize effectively. Addressing focus and emotional issues involves implementing structured meal plans, providing parents with guidance on educating their children, and fostering strong collaboration with teachers.